2011
DOI: 10.3109/07388551.2010.543967
|View full text |Cite
|
Sign up to set email alerts
|

Recent status and prospects of the fungal immunomodulatory protein family

Abstract: With the exception of polysaccharides and triterpenes/triterpenoids compounds, fungal immunomodulatory protein (FIP), a small molecule protein, is also an important bioactive component with immune regulating activity. It plays a significant role in immunomodulating. The objective of this paper was to review the latest advances in various aspects of research on FIPs, including their basic components and structural character, characters of diversity, gene cloning and expression, and their biological function, et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 32 publications
0
58
0
Order By: Relevance
“…In this study b-glucan from Shiitake was used because many bioactive effects have been published, including protective effect towards tuberculosis infection in mice (Markova et al, 2003), prophylactic potential to malaria tested in mice (Zhou et al, 2009) and many more in which most effects are mediated via the inactivation of macrophages. FIPs were never tested in an E. coli infection model but have been tested in animal allergy models (Li et al, 2011;. These studies resulted in the hypothesis that these FIPs are potent immunomodulators skewing the immune balance towards Th1, which has an effect on the anaphylactic shock but might also modulate the immune response against intestinal infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study b-glucan from Shiitake was used because many bioactive effects have been published, including protective effect towards tuberculosis infection in mice (Markova et al, 2003), prophylactic potential to malaria tested in mice (Zhou et al, 2009) and many more in which most effects are mediated via the inactivation of macrophages. FIPs were never tested in an E. coli infection model but have been tested in animal allergy models (Li et al, 2011;. These studies resulted in the hypothesis that these FIPs are potent immunomodulators skewing the immune balance towards Th1, which has an effect on the anaphylactic shock but might also modulate the immune response against intestinal infections.…”
Section: Discussionmentioning
confidence: 99%
“…Xue et al (2008) and Liang et al (2009) have shown that these FIPs can be expressed in Pichia, while retaining bioactivity. Although studied FIPs such as LZ8, FIP-five, FIP-Vvo and all other FIPs identified have a high degree of similarity at the protein level, they all have different specificity and activity in haemagglutination depending on the species origin of the blood (Li et al, 2011). It would be worth testing the specificity of the LZ9 and other FIPs towards chicken red blood cells and based on these results select a potential best-fitted FIP for future experiments with birds.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been prescribed to prevent and treat various human diseases, particularly in China, Japan, and Korea (Boh, 2013). Various bioactive substances have been isolated and identified from G. lucidum, such as triterpenoids (Wu et al, 2013), polysaccharides (Xu et al, 2011), and fungal immunomodulatory proteins (Li et al, 2011). G. lucidum was described by Curtis based on material from England and the epithet was sanctioned by Fries (Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these proteins exhibit a high structural and functional similarity with the immunoglobulin superfamily (Li et al, 2011a). Since the first FIP was isolated and characterized from G. lucidum (LZ-8) , its biological functions have been intensively explored and its DNA and protein sequences have served as references for the identification of new FIPs in other fungi, through homology hypotheses.…”
Section: Introductionmentioning
confidence: 99%
“…This immunomodulation is mediated in part by proteins of the Fungal Immunomodulatory Protein (FIP) family, among other therapeutic secondary metabolites. The biological function and action mechanisms of these proteins have been reported extensively in diverse studies (Li et al, 2011a;Li et al, 2010a;Lin, 2005), classifying them as possible effective agents for treating and preventing diseases originated by certain immunodeficiencies and other states of immune dysfunction.…”
Section: Introductionmentioning
confidence: 99%